A CERTAIN SUBCLASS OF MULTIVALENT ANALYTIC FUNCTIONS WITH NEGATIVE COEFFICIENTS FOR OPERATOR ON HILBERT SPACE - Wanas, Abbas Kareem (Journal of the Indonesian Mathematical Society, 2015)
By making use of the operators on Hilbert space, we introduce and studya subclass Ak of multivalent analytic functions with negative coecients. Also we obtain some geometric properties.DOI :Â http://dx.doi.org/10.22342/jims.21.2.228.77-82Â